Constraints in code-switching: a case study from Basque and Spanish - Arrate Isasi-Isasmendi; Irantzu Epelde (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
In the present study we analyze two features in Basque-Spanish code-switching data: (1) phonological mixing in intraword position involving phoneme /θ/ and (2) switches between pronouns and verbs. Both features have been discussed for several language pairs but have so far remained unexplored in the case of Basque and Spanish. The MELAN corpus on Basque-Spanish language contact is used in this study to obtain code-switching data and test the predictions of the two most influential theoretical frameworks for code-switching (the Matrix Language Frame (MLF) model and the Minimalist Approach) for these particular features. The results at the phonological level reveal that Basque-Spanish code-switching resembles most other language pairs in avoiding phonemes from different phonological systems within words, although counter-examples are found and should probably be interpreted as signals of sound change in Basque. Conversely, the results from the analysis of pronoun-verb switch cases reveal that in Basque-Spanish data, switches take place in positions disallowed by current models and unaccepted in several other language pairs. The findings suggest that the ergative case marking in Basque may play a role in the grammaticality of the pronoun-verb switch patterns.